Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 23 May 2017, 14:27

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

M10: Q21 - PS

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
Manager
Joined: 23 Jun 2008
Posts: 140
Followers: 3

Kudos [?]: 114 [0], given: 0

M10: Q21 - PS [#permalink]

Show Tags

22 Aug 2008, 15:37
3
This post was
BOOKMARKED
If function $$F(x)$$ satisfies $$F(x) = F(x^2)$$ for all $$x$$ , which of the following must be true?

(A) $$F(4) = F(2)*F(2)$$
(B) $$F(16) - F(-2) = 0$$
(C) $$F(-2) + F(4) = 0$$
(D) $$F(3) = 3*F(3)$$
(E) $$F(0) = 0$$

[Reveal] Spoiler: OA
B

Source: GMAT Club Tests - hardest GMAT questions

Between B and E, which one is correct and why?
Manager
Joined: 20 May 2008
Posts: 57
Followers: 2

Kudos [?]: 16 [0], given: 1

Re: M10: Q21 - PS [#permalink]

Show Tags

23 Aug 2008, 03:32
balboa wrote:
Function F(x) satisfies F(x) = F(x^2) for all x. Which of the following must be true?

a) F(4) = F(2) * F(2)
b) F(16) - F(-2) = 0
c) F(-2)+F(4) = 0
d) F(3) = 3*F(3)
e) F(0) = 0

Given : F(x) = F (x^2)
F(-2) = F (-2^2) = F (4)
F(4) = F(4^2) = F(16)

Therefore, F(16) - F(-2) = F (16) - F(16)=0

Ans is B
Manager
Joined: 20 May 2008
Posts: 57
Followers: 2

Kudos [?]: 16 [0], given: 1

Re: M10: Q21 - PS [#permalink]

Show Tags

23 Aug 2008, 23:58
You cant come to the conclusion that F(0) = 0 There is not information given about the vlaue of F(x).

Whats the OA?
Intern
Joined: 19 Jun 2008
Posts: 20
Followers: 0

Kudos [?]: 21 [1] , given: 0

Re: M10: Q21 - PS [#permalink]

Show Tags

30 Aug 2008, 12:35
1
KUDOS
LoyalWater wrote:
balboa wrote:
Function F(x) satisfies F(x) = F(x^2) for all x. Which of the following must be true?

a) F(4) = F(2) * F(2)
b) F(16) - F(-2) = 0
c) F(-2)+F(4) = 0
d) F(3) = 3*F(3)
e) F(0) = 0

Given : F(x) = F (x^2)
F(-2) = F (-2^2) = F (4)
F(4) = F(4^2) = F(16)

Therefore, F(16) - F(-2) = F (16) - F(16)=0

Ans is B

I don't understand why F(-2) is taken to the 4th power....when the original function states that is to be taken to the 2nd power.
CIO
Joined: 02 Oct 2007
Posts: 1218
Followers: 97

Kudos [?]: 946 [0], given: 334

Re: M10: Q21 - PS [#permalink]

Show Tags

01 Sep 2008, 01:15
Refer to the second post in this thread. The trick is here:

F(-2)=F(4)
and also
F(4)=F(16)
therefore
F(-2)=F(16)

I hope this helps.
_________________

Welcome to GMAT Club!

Want to solve GMAT questions on the go? GMAT Club iPhone app will help.
Please read this before posting in GMAT Club Tests forum
Result correlation between real GMAT and GMAT Club Tests
Are GMAT Club Test sets ordered in any way?

Take 15 free tests with questions from GMAT Club, Knewton, Manhattan GMAT, and Veritas.

GMAT Club Premium Membership - big benefits and savings

Manager
Joined: 09 Jul 2007
Posts: 243
Followers: 3

Kudos [?]: 240 [0], given: 0

Re: M10: Q21 - PS [#permalink]

Show Tags

02 Sep 2008, 14:04
It does not provide information about the value of F(x) or F(x^2) .. so we can not perform any operation with F(x) or F(x^2).
The leaves us only F(16) - F(-2) = 0 and F(-2)+F(4) = 0 to be examined..

F(x) = F(x^2) => f(-2) = f(4) =f(16) .. so B is the answer.
Manager
Joined: 04 Dec 2009
Posts: 70
Location: INDIA
Followers: 2

Kudos [?]: 9 [0], given: 4

Re: M10: Q21 - PS [#permalink]

Show Tags

12 Apr 2010, 20:51
hear F(x)=F(x^2) but not any specific operation so,

F(x) = F(x^2) => f(-2) = f(4) =f(16) .. so B is the answer.
_________________

MBA (Mind , Body and Attitude )

SVP
Joined: 16 Nov 2010
Posts: 1666
Location: United States (IN)
Concentration: Strategy, Technology
Followers: 34

Kudos [?]: 533 [0], given: 36

Re: M10: Q21 - PS [#permalink]

Show Tags

14 Apr 2011, 06:50
F(-2) = F((-2)^2) = F(4)

F(4) = F(4^2) = F(16)

=> F(16) - F(-2) = 0

_________________

Formula of Life -> Achievement/Potential = k * Happiness (where k is a constant)

GMAT Club Premium Membership - big benefits and savings

Manager
Status: It's "Go" Time.......
Affiliations: N.C.C.
Joined: 22 Feb 2011
Posts: 181
Location: India
Followers: 6

Kudos [?]: 74 [0], given: 2

Re: M10: Q21 - PS [#permalink]

Show Tags

16 Apr 2011, 14:50
Just by going the same logic why "C" cant be the answer?

As (-2)^2 = 4
_________________

We are twice armed if we fight with faith.

He who knows when he can fight & when He can't will be victorious.

Manager
Joined: 15 Apr 2011
Posts: 65
Location: Bangalore India
Schools: LBS, HBS, ISB, Kelloggs, INSEAD
Followers: 2

Kudos [?]: 7 [0], given: 2

Re: M10: Q21 - PS [#permalink]

Show Tags

19 Apr 2011, 02:18
vijayahir wrote:
Just by going the same logic why "C" cant be the answer?

As (-2)^2 = 4

Because F(4) + f(4) can not be equal to zero unless F(4) = 0 which we have no information about, so the answer can not be C.
_________________

Thanks,
AM

Intern
Joined: 06 Apr 2011
Posts: 42
Followers: 0

Kudos [?]: 36 [0], given: 4

Re: M10: Q21 - PS [#permalink]

Show Tags

21 Apr 2011, 17:57
balboa wrote:
If function $$F(x)$$ satisfies $$F(x) = F(x^2)$$ for all $$x$$ , which of the following must be true?

(A) $$F(4) = F(2)*F(2)$$
(B) $$F(16) - F(-2) = 0$$
(C) $$F(-2) + F(4) = 0$$
(D) $$F(3) = 3*F(3)$$
(E) $$F(0) = 0$$

[Reveal] Spoiler: OA
B

Source: GMAT Club Tests - hardest GMAT questions

Between B and E, which one is correct and why?

If for some reason the answer is B, why not A?
We are saying F(-2) = F(4) = F(16) and therefore F(16) - F(-2) => F(16) - F(16) =0 must be true.
So in the above example we are doing a simple arithmetic of 16 - 16 for F(16) - F(16).

Why not do 4 = 2 * 2 for F(4) = F(2)*F(2)? Can someone please help explain?
Math Forum Moderator
Joined: 20 Dec 2010
Posts: 2013
Followers: 163

Kudos [?]: 1822 [0], given: 376

Re: M10: Q21 - PS [#permalink]

Show Tags

22 Apr 2011, 00:36
mniyer wrote:
balboa wrote:
If function $$F(x)$$ satisfies $$F(x) = F(x^2)$$ for all $$x$$ , which of the following must be true?

(A) $$F(4) = F(2)*F(2)$$
(B) $$F(16) - F(-2) = 0$$
(C) $$F(-2) + F(4) = 0$$
(D) $$F(3) = 3*F(3)$$
(E) $$F(0) = 0$$

[Reveal] Spoiler: OA
B

Source: GMAT Club Tests - hardest GMAT questions

Between B and E, which one is correct and why?

If for some reason the answer is B, why not A?
We are saying F(-2) = F(4) = F(16) and therefore F(16) - F(-2) => F(16) - F(16) =0 must be true.
So in the above example we are doing a simple arithmetic of 16 - 16 for F(16) - F(16).

Why not do 4 = 2 * 2 for F(4) = F(2)*F(2)? Can someone please help explain?

We don't know what the function actually returns; we just know that the function returns the same value for a number and its square.

e.g..

f(2^{1/4})=100
f(2^{1/2})=100
f(2)=100
f(4)=100
f(16)=100

OR

f(2^{1/4})=2
f(2^{1/2})=2
f(2)=2
f(4)=2
f(16)=2

AND
f(3^{1/4})=200
f(3^{1/2})=200
f(3)=200
f(9)=200
f(81)=200

Now,
f(4) = f(2)*f(2)

If;
f(2)=0
f(4)=0
f(16)=0

f(2)*f(2)=0
f(4) = f(2)*f(2) as 0 = 0.

If,
f(2)=2
f(4)=2
f(16)=2
f(2)*f(2)=2*2=4

f(4) != f(2)*f(2) as 2 != 4

So, this function may be true but not MUST be true.
_________________
Senior Manager
Joined: 24 Mar 2011
Posts: 450
Location: Texas
Followers: 5

Kudos [?]: 183 [0], given: 20

Re: M10: Q21 - PS [#permalink]

Show Tags

08 May 2011, 12:48
What if one of the option is f(-2)-f(4)=0
Math Forum Moderator
Joined: 20 Dec 2010
Posts: 2013
Followers: 163

Kudos [?]: 1822 [0], given: 376

Re: M10: Q21 - PS [#permalink]

Show Tags

08 May 2011, 12:50
agdimple333 wrote:
What if one of the option is f(-2)-f(4)=0

This will also be correct.
_________________
Senior Manager
Joined: 30 Jun 2011
Posts: 267
Followers: 0

Kudos [?]: 75 [0], given: 20

Re: M10: Q21 - PS [#permalink]

Show Tags

18 Apr 2012, 06:04
balboa wrote:
Do you mind telling me how E is incorrect?

Because there are many possibilities other than one given what if F(x) = 1 then F(0)=1
Manager
Joined: 27 Apr 2010
Posts: 121
Followers: 0

Kudos [?]: 94 [0], given: 61

Re: M10: Q21 - PS [#permalink]

Show Tags

19 Apr 2012, 14:31
the key to solving this problem is that if not given a restriction as in b... the function can go on forever right?
Math Expert
Joined: 02 Sep 2009
Posts: 38841
Followers: 7718

Kudos [?]: 105918 [8] , given: 11593

Re: M10: Q21 - PS [#permalink]

Show Tags

19 Apr 2012, 14:37
8
KUDOS
Expert's post
1
This post was
BOOKMARKED
snkrhed wrote:
the key to solving this problem is that if not given a restriction as in b... the function can go on forever right?

Below is a detailed solution of this problem. Hope it helps.

If function $$f(x)$$ satisfies $$f(x) = f(x^2)$$ for all $$x$$, which of the following must be true?
A. $$f(4) = f(2)f(2)$$
B. $$f(16) - f(-2) = 0$$
C. $$f(-2) + f(4) = 0$$
D. $$f(3) = 3f(3)$$
E. $$f(0) = 0$$

We are told that some function $$f(x)$$ has following property $$f(x) = f(x^2)$$ for all values of $$x$$. Note that we don't know the actual function, just this one property of it. For example for this function $$f(3)=f(3^2)$$ --> $$f(3)=f(9)$$, similarly: $$f(9)=f(81)$$, so $$f(3)=f(9)=f(81)=...$$.

Now, the question asks: which of the following MUST be true?

A. $$f(4)=f(2)*f(2)$$: we know that $$f(2)=f(4)$$, but it's not necessary $$f(2)=f(2)*f(2)$$ to be true (it will be true if $$f(2)=1$$ or $$f(2)=0$$ but as we don't know the actual function we can not say for sure);

B. $$f(16) - f(-2) = 0$$: again $$f(-2)=f(4) =f(16)=...$$ so $$f(16)-f(-2)=f(16)-f(16)=0$$ and thus this option is always true;

C. $$f(-2) + f(4) = 0$$: $$f(-2)=f(4)$$, but it's not necessary $$f(4) + f(4)=2f(4)=0$$ to be true (it will be true only if $$f(4)=0$$, but again we don't know that for sure);

D. $$f(3)=3*f(3)$$: is $$3*f(3)-f(3)=0$$? is $$2*f(3)=0$$? is $$f(3)=0$$? As we don't know the actual function we can not say for sure;

E. $$f(0)=0$$: And again as we don't know the actual function we can not say for sure.

_________________
Manager
Status: Applying
Joined: 01 Dec 2012
Posts: 92
Location: United States (OH)
Concentration: Strategy, Entrepreneurship
GMAT 1: 750 Q50 V42
GPA: 2.9
WE: Consulting (Consulting)
Followers: 11

Kudos [?]: 86 [0], given: 67

Re: M10: Q21 - PS [#permalink]

Show Tags

19 Apr 2013, 06:27
Bunuel wrote:
snkrhed wrote:
the key to solving this problem is that if not given a restriction as in b... the function can go on forever right?

Below is a detailed solution of this problem. Hope it helps.

If function $$f(x)$$ satisfies $$f(x) = f(x^2)$$ for all $$x$$, which of the following must be true?
A. $$f(4) = f(2)f(2)$$
B. $$f(16) - f(-2) = 0$$
C. $$f(-2) + f(4) = 0$$
D. $$f(3) = 3f(3)$$
E. $$f(0) = 0$$

We are told that some function $$f(x)$$ has following property $$f(x) = f(x^2)$$ for all values of $$x$$. Note that we don't know the actual function, just this one property of it. For example for this function $$f(3)=f(3^2)$$ --> $$f(3)=f(9)$$, similarly: $$f(9)=f(81)$$, so $$f(3)=f(9)=f(81)=...$$.

Now, the question asks: which of the following MUST be true?

A. $$f(4)=f(2)*f(2)$$: we know that $$f(2)=f(4)$$, but it's not necessary $$f(2)=f(2)*f(2)$$ to be true (it will be true if $$f(2)=1$$ or $$f(2)=0$$ but as we don't know the actual function we can not say for sure);

B. $$f(16) - f(-2) = 0$$: again $$f(-2)=f(4) =f(16)=...$$ so $$f(16)-f(-2)=f(16)-f(16)=0$$ and thus this option is always true;

C. $$f(-2) + f(4) = 0$$: $$f(-2)=f(4)$$, but it's not necessary $$f(4) + f(4)=2f(4)=0$$ to be true (it will be true only if $$f(4)=0$$, but again we don't know that for sure);

D. $$f(3)=3*f(3)$$: is $$3*f(3)-f(3)=0$$? is $$2*f(3)=0$$? is $$f(3)=0$$? As we don't know the actual function we can not say for sure;

E. $$f(0)=0$$: And again as we don't know the actual function we can not say for sure.

Great explanation! I missed out on the initial part and got lost (f'x is the same as f'x2 the same as f'x4) - Great question!

Thanks & Regards,
Vishnu
_________________

Regards,
Vishnu

Article --> http://www.topmba.com/blog/could-mba-degree-be-way-forward

Intern
Joined: 12 Apr 2013
Posts: 8
Location: Germany
Concentration: Finance, Accounting
GMAT Date: 05-28-2013
GPA: 3.6
Followers: 0

Kudos [?]: 11 [2] , given: 20

Re: M10: Q21 - PS [#permalink]

Show Tags

21 Apr 2013, 10:15
2
KUDOS
When F(x) = F(x²) for all x, then F must be a constant function. That means F(0)=F(1)=F(...) whatever.
That is why B must be correct.
_________________

........................................................................................
See it big and keep it simple.

Manager
Joined: 01 Feb 2012
Posts: 86
Followers: 0

Kudos [?]: 39 [0], given: 150

Re: M10: Q21 - PS [#permalink]

Show Tags

23 Apr 2013, 10:03
Bunuel wrote:
snkrhed wrote:
the key to solving this problem is that if not given a restriction as in b... the function can go on forever right?

Below is a detailed solution of this problem. Hope it helps.

If function $$f(x)$$ satisfies $$f(x) = f(x^2)$$ for all $$x$$, which of the following must be true?
A. $$f(4) = f(2)f(2)$$
B. $$f(16) - f(-2) = 0$$
C. $$f(-2) + f(4) = 0$$
D. $$f(3) = 3f(3)$$
E. $$f(0) = 0$$

We are told that some function $$f(x)$$ has following property $$f(x) = f(x^2)$$ for all values of $$x$$. Note that we don't know the actual function, just this one property of it. For example for this function $$f(3)=f(3^2)$$ --> $$f(3)=f(9)$$, similarly: $$f(9)=f(81)$$, so $$f(3)=f(9)=f(81)=...$$.

Now, the question asks: which of the following MUST be true?

A. $$f(4)=f(2)*f(2)$$: we know that $$f(2)=f(4)$$, but it's not necessary $$f(2)=f(2)*f(2)$$ to be true (it will be true if $$f(2)=1$$ or $$f(2)=0$$ but as we don't know the actual function we can not say for sure);

B. $$f(16) - f(-2) = 0$$: again $$f(-2)=f(4) =f(16)=...$$ so $$f(16)-f(-2)=f(16)-f(16)=0$$ and thus this option is always true;

C. $$f(-2) + f(4) = 0$$: $$f(-2)=f(4)$$, but it's not necessary $$f(4) + f(4)=2f(4)=0$$ to be true (it will be true only if $$f(4)=0$$, but again we don't know that for sure);

D. $$f(3)=3*f(3)$$: is $$3*f(3)-f(3)=0$$? is $$2*f(3)=0$$? is $$f(3)=0$$? As we don't know the actual function we can not say for sure;

E. $$f(0)=0$$: And again as we don't know the actual function we can not say for sure.

Hi Bunuel,

thanks for the explanation. I found this question to be very tough and I seem to be the only one not being able to understand this even after your explanation

I could understand why B is the answer and why not C and D. But I am still confused with A and E. I have tried to explain my thought process below -

We know that f(x) = f(x^2) means f(2) = f(4) = f(16) and so on.....
A. f(4)=f(2)*f(2)
LHS is f(4) which means (16)
RHS is f(2)*f(2) means 4*4 means (16)
Hence LHS = RHS?
As I am writing this, it occurred to me that here we are multiplying to functions {f(2)*f(2)} and we don't really know if multiplying of two functions will actually result in the multiplication of those two numbers/integers? it could result in some other function as well? Am I thinking in the right direction?

Coming to option E - it says f(0)=0
we know that f(x) = f(x^2)
if x is 0...its square (infact any exponent) or function of its square should always result in 0. I can't think through what's wrong with E?

Could you please help me understand where I am going wrong. Many thanks for your help.

Kind regards
Re: M10: Q21 - PS   [#permalink] 23 Apr 2013, 10:03

Go to page    1   2    Next  [ 23 posts ]

Similar topics Replies Last post
Similar
Topics:
3 m01-q 21 4 12 Mar 2013, 07:13
1 V02 - Q21 1 17 Jun 2010, 03:53
M09 Q21 1 26 Sep 2010, 03:59
m09 q 21 1 24 Sep 2009, 00:59
8 M10: Q24 - PS 9 18 Jun 2013, 07:57
Display posts from previous: Sort by

M10: Q21 - PS

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

Moderator: Bunuel

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.